The Role of The Principal in Improving the Quality of Education Through School-Community Relations Management at MI Persis Gandok Tasikmalaya City - Mahmudin, Wildan; Maulana Restu, Yanto; Nahar, Agus Samsul; Erihadiana, Mohamad; Al-fajar, Fahrurroji Firman (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2024)
The aim of this research is to determine Public Relations management at MI Persis Gandok City. Tasikmalaya. Meanwhile, the specific aim is to describe the planning of school and community relations, the implementation of school and community relations and how the principal evaluates the implementation of school and community relations. The research method used in this research is qualitative descriptive research. MI Persis Gandok is planning several public relations work programs, among which the Public Relations Program is to form cooperation in the field of strengthening educational institutions through the formation of Madrasah Councils and Congregational Leadership. Through the formation of madrasah councils and congregational leaders, they can provide a bridge in the form of communication between the school and the community. To make the MI Persis Gandok school public relations program a success, there are several techniques that can be used. The technique chosen is a technique that is considered effective and efficient according to school conditions, the condition of the students' parents, the condition of the surrounding community, and the school's finances. Among these techniques are: group face-to-face meeting techniques, individual face-to-face meeting techniques and school publication techniques. One form of evaluation by the Principal of MI Persis Gandok towards Madrasah Public Relations is through observation, checklists, questionnaires and/or through meetings/briefings. The objectives of this evaluation are: 1) To ensure that the entire program is known; 2) Ensure that the Madrasah's image in society has good values; 3) make a follow-up to the evaluation results.